The Effect of Curing Time on Water Content in the Metal Casting Process - Nuraeni Suryaman, Nia; Santoso, Heru; Prasetia, Adhita (International Journal of Psychosocial Rehabilitation, 2020)
Silica sand is one type of sand that is often used by industries engaged in metal casting. This is because silica sand is used as a molding material. Besides being easily formed, this silica sand, when mixed with chemicals such as resins and catalysts, will achieve maximum hardness. In order to achieve the maximum strength of the sand mold, a curing time process is needed. After the molding material is mixed and stirred, the drying time starts to be calculated. Achieve maximum strength because the mixture reacts during curing time. This study aims to observe and study the effect of differences in curing time on the water content of alphase molds. Curing time variations are at 2 hours, 4 hours, 6 hours, 8 hours, 24 hours, 48 hours, and 72 hours. This research went through several stages of testing, including sand distribution testing, compression testing, water content testing, LOI testing, and SEM testing. The focus of this research is testing the water content. A good sample used for alphaset molding is one that has no water content. The results showed that samples that could be used were those that had curing times of 6 hours, 8 hours, and 72 hours. This is because at the curing time it has a water content of 0%.